Towards new ways of being and thinking of being male in a group of young k-pop followers in Lima: an analysis on the construction of an emerging masculinity - Barrera Ugarte, Alejandra (2022)
This article studies the masculinity construction process of young male fans of k-pop in Lima. K-pop is a Korean music genre whose expansion has generated a massive cultural phenomenon. To understand this process, first we present the models and representations of masculinity that these men perceive in the artists and in Lima society to later establish how they relate to these models through the construction of their own masculinity. In this sense, the following was analysed: a) how they define and evaluate the masculinity of k-pop idols; b) how these young men understand the Lima masculinity model and how they relate to it; and c) what is the balance that they make of these representations and, based on this, how they think, build and live their own masculinity. In this qualitative and ethnographic study, the methodological criteria used for the selection of the interviewees were randomisation, as well as convenience and snowball sampling. Regarding the collection of information, in-depth semi-structured interviews were carried out.